An Unusual Association: Total Anomalous Pulmonary Venous Return and Aortic Arch Obstruction in Patients with Cat Eye Syndrome - Williams, Jason L.; McDonald, Marie T.; Seifert, Bryce A.; Deak, Kristen L.; Rehder, Catherine W.; Campbell, Michael J. (Journal of Pediatric Genetics, 2020)
Cat eye syndrome (CES) is a rare genetic defect, characterized by iris colobomas, preauricular skin tags, and anal malformations. Affecting 1 in 150,000 people, this defect is caused by duplication or triplication of the proximal long (q) arm of chromosome 22. Congenital heart disease is associated with CES. One of the most common heart defects in patients with CES is total anomalous pulmonary venous return (TAPVR). In this article, we reported patients with a rare association of concomitant TAPVR and aortic arch obstruction: one with interrupted aortic arch and the other with coarctation of the aorta with an aberrant right subclavian artery.
Keywords: cat eye syndrome; pulmonary vein; transthoracic echocardiogram; interrupted aortic arch